HIV Screening Among Gonorrhea-Diagnosed Individuals; Baltimore, Maryland; April 2015 to April 2019 - Williford, Sarah L; Humes, Elizabeth; Greenbaum, Adena; Schumacher, Christina M (Sexually transmitted diseases, 2021)
Individuals diagnosed with gonorrhea are at elevated risk for HIV. Per US Centers for Disease Control and Prevention guideline, individuals being evaluated for gonorrhea should be screened for HIV concurrently. There is limited information on HIV screening among gonorrhea-diagnosed individuals across different health care settings. Our objective was to identify potential gaps in HIV screening among gonorrhea-diagnosed individuals in Baltimore City, Maryland. We used Sexually Transmitted Disease Surveillance Network project data collected on a random sample of all gonorrhea diagnoses reported to the health department between April 2015 and April 2019. Individuals with known HIV diagnoses were excluded. HIV screening was confirmed through surveys administered to the gonorrhea-diagnosing provider. HIV screening across groups was assessed using Poisson regression models with robust SEs. We examined those with and without recent (≤12 months) sexually transmitted infection (STI) history separately. Among 2830 gonorrhea-diagnosed individuals with completed Sexually Transmitted Disease Surveillance Network provider surveys, less than half (35.2% with and 44.8% without recent STI history) received concurrent HIV screening. HIV screening was 73% less prevalent among those diagnosed in emergency departments/urgent care centers/hospitals versus sexual health clinics (with and without recent STI history: adjusted prevalence ratio, 0.27 [95% confidence interval, 0.19-0.39]; adjusted prevalence ratio, 0.27 [0.23-0.33]), controlling for diagnosis year, sex, race/ethnicity, age, infection site, and insurance. Our findings suggest a considerable gap in HIV screening among individuals at elevated risk for HIV acquisition in Baltimore City, particularly among those diagnosed in emergency departments/urgent care centers/hospital settings. Future work should focus on identifying provider-level barriers to concurrent HIV/STI screening to inform provider education programs.